A robust control analysis for a steer-by-wire vehicle with uncertainty on the tyre forces. Issue 9 (1st September 2016) - van der Sande, T.; Zegelaar, P.; Besselink, I.; Nijmeijer, H.
ABSTRACT: This paper proposes guidelines for controller design for steer-by-wire vehicles. The proposed controller removes the velocity dependency of the vehicle dynamics and accounts for the nonlinear characteristics of the lateral tyre force. Using an approach, bounds on the closed loop sensitivity are presented, which results in guidelines for the controller design. Using the designed controller, simulations using a multi-body model show that the yaw dynamics of the vehicle are stabilised for extreme manoeuvres.